Grain boundary light beam induced current: A characterization of bonded silicon wafers and polycrystalline silicon thin films for diffusion length extraction. Issue 7 (13th April 2016) - Gref, Orman; Teodoreanu, Ana‐Maria; Leihkauf, Rainer; Lohrke, Heiko; Kittler, Martin; Amkreutz, Daniel; Boit, Christian; Friedrich, Felice
Abstract : The charge carrier lifetime and accordingly the diffusion length in polycrystalline semiconductor materials is known to be detrimentally influenced by disordered interfaces like grain boundaries (GBs). The GB light beam induced current (GB‐LBIC) technique is suitable for the extraction of the minority charge carrier diffusion length in unprocessed polycrystalline materials. This measurement method is based on the GB itself acting as a charge collector. A spatially‐resolved light beam induced current can thus be measured even without a collecting p–n junction or Schottky contact, and without biasing the sample. In this contribution we present a simulation based analysis of measured GB‐LBIC line scans on bonded silicon wafers and polycrystalline silicon thin films with different laser wavelengths and intensities.